A dynamic programming algorithm for the buffer allocation problem in homogeneous asymptotically reliable serial production lines. Issue 3 (15th September 2004) - Diamantidis Diamantidis, A. C. A. C.; Papadopoulos Papadopoulos, C. T. C. T.
Abstract : In this study, the buffer allocation problem (BAP) in homogeneous, asymptotically reliable serial production lines is considered. A known aggregation method, given by Lim, Meerkov, and Top (1990), for the performance evaluation (i.e., estimation of throughput) of this type of production lines when the buffer allocation is known, is used as an evaluative method in conjunction with a newly developed dynamic programming (DP) algorithm for the BAP. The proposed algorithm is applied to production lines where the number of machines is varying from four up to a hundred machines. The proposed algorithm is fast because it reduces the volume of computations by rejecting allocations that do not lead to maximization of the line's throughput. Numerical results are also given for large production lines.